1987
DOI: 10.1200/jco.1987.5.8.1150
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of 5-fluorouracil and high-dose intravenous leucovorin in gastric carcinoma.

Abstract: Twenty-eight patients with advanced measurable gastric carcinoma were treated with leucovorin (dl-CF; folinic acid; dl-5-formyltetrahydrofolic acid) 500 mg/m2 administered as a two-hour infusion and 5-fluorouracil (5-FU) 600 mg/m2 intravenous (IV) push midinfusion. Treatment was administered weekly for 6 weeks followed by a 2-week rest. Twenty-five patients were evaluable for response. Twelve of them had received previous combination chemotherapy that included 5-FU. Median age was 59 years, and median Eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…The response rate seen was in accord with those obtained in other colorectal cancer studies (De Gramont et al, 1988;Petrelli et al, 1988;Petrelli et al, 1989;Poon et al, 1989;Machover et al, 1986;Erlichman et al, 1988;Arbuck, 1989), suggesting similar efficacy, although clearly a phase III trial would be required to confirm this. The response rate in gastric cancers is comparable to that described for more toxic combination regimens (Macdonald et al, 1979;Gastrointestinal Tumor Study Group 1982;Douglass et al, 1984) and considerably better than that reported previously for 5-fluourouracil and folinic acid (Arbuck et al, 1987;Berenberg et al, 1989). Although the numbers treated are small it certainly appears worthy of further evaluation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The response rate seen was in accord with those obtained in other colorectal cancer studies (De Gramont et al, 1988;Petrelli et al, 1988;Petrelli et al, 1989;Poon et al, 1989;Machover et al, 1986;Erlichman et al, 1988;Arbuck, 1989), suggesting similar efficacy, although clearly a phase III trial would be required to confirm this. The response rate in gastric cancers is comparable to that described for more toxic combination regimens (Macdonald et al, 1979;Gastrointestinal Tumor Study Group 1982;Douglass et al, 1984) and considerably better than that reported previously for 5-fluourouracil and folinic acid (Arbuck et al, 1987;Berenberg et al, 1989). Although the numbers treated are small it certainly appears worthy of further evaluation.…”
Section: Discussionsupporting
confidence: 68%
“…One phase II trial showed a response rate of 48% (Machover et al, 1986) but another only 12% (Arbuck et al, 1987) and a third 24% (Berenberg et al, 1989). These reports also describe toxicity different from that produced by 5-fluorouracil alone: Regimens using weekly bolus injections are reported as frequently causing diarrhoea (in 22-80% of patients) with occasional toxic deaths from this (Petrelli et al, 1988;Petrelli et al, 1989), whilst those employing daily injections for one week in four report both diarrhoea and oral mucositis -the latter in 40-80% of patients (Machover et al, 1986;Erlichman et al, 1988;Poon et al, 1989).…”
mentioning
confidence: 99%
“…5-FU monotherapy, a standard treatment in Japan, is associated with a response rate of approximately 20% and an overall survival time of between 5 and 7 months in phase III randomized studies (8,9). The modulation of 5-FU with leucovorin has generally enhanced the antitumor efficacy (10,11), and has been shown to have activity in patients who had previously progressed on 5-FU-containing combinations (12).…”
Section: Single Agent Chemotherapymentioning
confidence: 99%
“…The choice of these drugs and schedule was made based on the following: 5-FU, epiADR and CDDP remain the most active single agents in gastric cancer (Schipper and Wagener, 1996); 5-FU and CDDP are potentially synergistic (Leichman and Berry, 1991); LV can enhance 5-FU activity (Arbuck et al, 1987); weekly administration allows more drug to be administered per unit time, which minimizes side effects (Young, 1990); filgrastim may contribute to perform weekly administrations of drugs reducing the incidence of neutropenia. This weekly intensive regimen confirmed its activity also in locally advanced gastric cancer enabling resection on half of previously inoperable tumour with a moderate toxicity (Cascinu et al, 1998), and now a randomized trial in the adjuvant setting is being carried out in Italy.…”
mentioning
confidence: 99%